Polymer Catalysts Imprinted with Metal Ions as Biomimics of Metalloenzymes - Joanna Czulak; Anna Jakubiak-Marcinkowska; Andrzej Trochimczuk (Advances in Materials Science and Engineering)
This work presents the preparation and properties of molecularly imprinted polymers (MIPs) with catalytic centers that mimic the active sites of metalloenzymes. The MIP synthesis was based on suspension polymerization of functional monomers (4-vinylpyridine and acrylonitrile) with trimethylolpropane trimethacrylate as a crosslinker in the presence of transition metal ions and 4-methoxybenzyl alcohol as a template. Four metal ions have been chosen for imprinting from among the microelements that are the most essential in the native enzymes: Cu2+, Co2+, Mn2+, and Zn2+. To prepare catalysts, the required loading of metal ions was obtained during sorption process. The catalysts imprinted with Cu2+, Co2+, and Zn2+ were successfully used for hydroquinone oxidation in the presence of hydrogen peroxide. The Mn2+-imprinted catalyst showed no activity due to the insufficient metal loading. Cu2+ MIP showed the highest efficiency. In case of Cu- and Co-MIP catalysts, their activity was additionally increased by the use of surface imprinting technique.